STUDI KASUS ASUHAN KEPERAWATAN PADA IBU DENGAN DIAGNOSA MEDIS IMPENDING EKLAMPSIA POST SECTIO CAESAREA - Ika Rismawati; Dwi Sri Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Impending eclampsia is an obstetric emergency condition that occurs as a result of the progression of severe preeclampsia and carries the risk of seizures, impaired organ perfusion, and maternal death if not managed promptly and appropriately. This condition requires intensive monitoring and comprehensive nursing care to prevent further complications. This case study aims to describe the implementation of nursing care in a patient with a medical diagnosis of impending eclampsia post-cesarean section in the delivery ward. The method used was a descriptive case study with a nursing process approach encompassing assessment, nursing diagnosis, intervention, implementation, and evaluation. The subject of this case study was Mrs. M. with a medical diagnosis of impending eclampsia post-cesarean section accompanied by severe preeclampsia. The assessment findings showed that the patient had high blood pressure, surgical wound pain, physical weakness, and a history of intraoperative bleeding. The nursing diagnoses identified were acute pain, risk of ineffective cerebral perfusion, risk of shock, and impaired physical mobility. After three days of nursing care, the patient's condition showed improvement, characterized by reduced pain, more stable blood pressure, absence of seizures, normal bleeding limits, and gradually increased mobilization ability. Comprehensive nursing care is essential to support the recovery of patients with impending eclampsia post-cesarean section.